Analysis information security threats network standard IEEE 802.11 - Мехед, Дмитро Борисович; Ткач, Юлія Миколаївна; Базилевич, Володимир Маркович; Петренко, Тарас Анатолійович (Ukrainian Information Security Research Journal, 2015)
Nowadays wireless technologies are constantly evolving and penetrate the social life, gradually replacing the wire. Easy to use, lower cost of installation – are the main advantages of wireless systems. The technology of standard IEEE 802.11, also known as Wi-Fi is today’s most popular wireless technology. The number of users increases daily. However, information security data in this technology, first, inferior protection systems wired networks because of the existence of threats features wireless networks, and secondly insufficiently researched and tested. So the problem identification and analysis of threats to information security network standard IEEE 802.11 is relevant today. By analyzing threats we relied on foreign research scientists and practitioners companies in this area involved in the study of development threats and prevent them. Researches of the issue makes it possible to identify and classify potential threats and, subsequently, upgrade existing or develop new effective methods and measures against threats to information security.